Simulation of Two Phase Flow Mixing Co – Current in T Junction Using Comsol - Noori, Wallaa A.; AlTimimi, Dhiyaa A. Hussein; Kadhim, Bashar Jawad (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
The analysis, behavior of two-phase flow incompressible fluid in T-juction is done by using "A Computational Fluid Dynamic (CFD) model" that application division of different in industries. The level set method was based in “Finite Element method”. In our search the behavior of two phase flow (oil and water) was studed. The two-phase flow is taken to simulate by using comsol software 4.3. The multivariable was studying such as velocity distribution, share rate, pressure and the fraction of volume at various times.  The velocity was employed at the inlet (0.2633, 0.1316, 0.0547 and 0.0283 m/s) for water and (0.1316 m/s) for oil, over and above the pressure set at outlet as a boundary condition. It was observed through the program that the shear rate increased in the mixing area and begins to decrease after the mixing area, for the pressure suddenly decreases in the mixing area and after this area begins to decrease linearly with the length of the tube.